Preparation of Some mercurated Polyacrylamide and It’s Copolymers and Their Industrial Applications - Farah. Kh. H. Al-juboory; Ahmed A. H. Al-kadhimi (Kirkuk Journal of Science, 2017)
polyacrylamide and some of its copolymers with styrene and N-vinyl carbazole have been prepared by free radical polymerization and some chemical modifications by using bromine, xanthhydrol and mercuration with mercury oxide and mercuric acetate have been done on polyacrylamide and its copolymers. This study was carried out to remove dibenzothiophene from model light oil (benzene containing DBT, 3080 ppm. sulfur content) by using the mercurated polymers.The analysis of the resulting treated DBT solution to know the sulfur concentration was obtained by using atomic absorption The mercurated polymers were identified spectroscopicaly using infrared spectroscopy.